Dermolipectomies after bariatric procedures in the Public Health System: a long way to go - Antoninho José Tonatto; Jorge Luís de Moraes; Fabiola Grigoletto Lupion; Silvia Helena Mandu; Vanessa Sayuri Ogawa; Carolina Peressutti; Renato da Silva Freitas (Revista Brasileira de Cirurgia Plástica, 2022)
Introduction: Obesity is one of the main health problems faced by the population, and its incidence has gradually increased in recent decades. Amid the global obesity epidemic, bariatric procedures have increased significantly and, despite the growing number of post-bariatric procedures, these are not equivalent to the number of bariatric surgeries.Methods: Data were collected from the public health registry (DATASUS) between 2008 and 2019 to analyze the selected parameters, with an assessment of the main post-bariatric dermolipectomy techniques, their distribution in the national territory, their length of stay, their mortality, costs for the Public System, the comparison between post-bariatric dermolipectomies and the distribution of bariatric procedures in the national territory. Furthermore, dermolipectomies and the distribution of plastic surgeons in Brazil were compared.Results: An increase of 164% was evidenced in the number of post-bariatric dermolipectomies during the studied period. Post-bariatric abdominal dermolipectomy was the most performed procedure, accounting for 65% of the procedures, followed by brachial (14.8%), crural (14.7%) and circumferential (4.7%) dermolipectomy. There was an inequality in the distribution of post-bariatric procedures among Brazilian macro-regions, with the Southeast Region having the highest percentage (49.8%) of dermolipectomies. Conclusions: Despite the progressive increase in post-bariatric dermolipectomies, they did not follow the number of bariatric procedures in the national territory. Therefore, there is a need for a parallel growth between both so that there is complementation in treating these patients. Then, there might be an improvement in the distribution of dermolipectomies in the national territory, allowing more patients to benefit.